18.6. COUNTER-EXAMPLES AND CONJECTURES

295

18.5. Finite case

Theorem

1529

.

Let

n

be a finite set.

1

. id

Strd

A

[

n

]

=

ID

Strd

A

[

n

]

if

A

and

Z

are meet-semilattices and (

A

;

Z

) is a finitely

meet-closed filtrator.

2

. ID

Strd

A

[

n

]

=

id

Strd

A

[

n

]

if (

A

;

Z

) is a primary filtrator over a distributive lattice.

Proof.

1

.

L

GR

ID

Strd

A

[

n

]

L

GR ID

Strd

A

[

n

]

MEET

L

i

i

n

∪ {A}

A

l

i

n

L

i

u A 6

= 0

(by finiteness)

Z

l

i

n

L

i

u A 6

= 0

L

id

Strd

A

[

n

]

for every

L

Q

Z

.

2

.

L

GR

id

Strd

A

[

n

]

up

L

GR id

Strd

A

[

n

]

⇔ ∀

K

up

L

:

K

GR id

Strd

A

[

n

]

K

up

L

:

Z

l

i

n

K

i

A ⇔ ∀

K

up

L

:

Z

l

i

n

K

i

6 A ⇔

(by finiteness and theorem

311

)

K

up

L

:

A

l

i

n

K

i

6 A ⇔ A ∈

\

h

?

i

(

d

A

i

n

K

i

K

up

L

)

(by the formula for finite meet of filters, theorem

378

)

A ∈

\

h

?

i

A

l

i

n

L

i

⇔ ∀

K

A

l

i

n

L

i

:

A ∈

?K

⇔ ∀

K

A

l

i

n

L

i

:

A 6

K

(by separability of core, theorem

379

)

A

l

i

n

L

i

6 A ⇔

L

ID

Strd

A

[

n

]

.

Proposition

1530

.

Let (

A

;

Z

) be a finitely meet closed filtrator.

ID

Strd

A

[

n

]

and

id

Strd

A

[

n

]

are the same for finite

n

.

Proof.

Because

d

Z

i

dom

L

L

i

=

d

A

i

dom

L

L

i

for finitary

L

.

FiXme

: Are meets

defined?

18.6. Counter-examples and conjectures

The following example shows that the theorem

1485

can’t be strengthened:

Example

1531

.

For some multifuncoid

f

on powersets complete in argument

k

the following formula is false:

h

f

i

l

(

L

∪ {

(

k

;

F

X

)

}

) =

F

x

X

h

f

i

l

(

L

∪ {

(

k

;

x

)

}

) for every

X

P

P

k

,

L

Q

i

(arity

f

)

\{

k,l

}

F

i

.

Proof.

Consider multifuncoid

f

= Λ id

Strd

U

[3]

where

U

is an infinite set (of the

form

P

3

) and

L

= (

Y

) where

Y

is a nonprincipal filter on

U

.

h

f

i

0

(

L

∪ {

(

k

;

F

X

)

}

) =

Y

u

F

X

;

F

x

X

h

f

i

0

(

L

∪ {

(

k

;

x

)

}

) =

F

x

X

(

Y

u

x

).